Women and leadership around the world - Madsen, Susan R.; Ngunjiri, Faith Wambura; Longman, Karen A.; Cherrey, Cynthia (Women and leadership (Charlotte, N.C.), 2015)
Women and Leadership around the World is the third volume in a new series of books (Women and Leadership: Research, Theory, and Practice) that will is now being published to inform leadership scholars and practitioners. The purpose of this volume is to explore areas of women's leadership in four regions around the world: the Middle East, Europe, North America, and Asia Pacific. Hence, we have included 14 chapters that cover a wide range of important topics relevant to women and leadership within specific contexts around the world. Our goal for this volume is to provide readers with explorations of women's experiences as leaders, including recent research studies, analysis and interpretation of statistics unpacking the status of women in various sectors and countries, stories of influential women leaders with national or local spheres of influence, and including recommendations for positive change to increase women's access to positions of authority. The volume contributors use various theories and conceptualizations to problematize, historicize, and analyze women's limited access to power, and their agency as leaders from the grassroots to the national scene, from education to non-profits and business organizations.Overall, the book contributes interpretations of the status of women in various countries, presenting the stories behind the numbers and statistics and uncovering not only challenges but also opportunities for resiliency and effectiveness as leaders. The authors offer recommendations for change that cross national boundaries, such as structural changes in organizations that would open the door for more women to access positions of authority and be effective as leaders. It is rare to find a book with such a diverse array of topics and countries, making this a timely contribution to the literature on women and leadership. The authors remind us to continue to expand the literature base on women and leadership, drawing from both qualitative and quantitative studies as well as conceptual explorations of women as leaders in different countries, regions, indigenous communities, and across different sectors. The more we know, the better informed will be our efforts to create appropriate leadership development activities and experiences for emerging women leaders and girls around the world. This book contributes significantly to that very effort.